ARTISTIC INTERPRETATION OF THE PERSONALITY OF THE POET IN THE POETRY OF ALISHER NAVOY - Raximova Gulbaxor; Bahriddinova Yulduz (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In the composition of an artistic work, which is the fruit of the creator's spiritual world, in some way, his personality is also involved. Because, the creative personifies his impressions from life, his attitude to reality, his pain, his armory of dreams, his hope and his love through his artistic works. That is why the value of a work of art is great when studying the personality of each creator. The article artistically explores the life of the great poet Alisher Navoi’s Highness, examples of poems in which socio-political activity is expressed.